(untitled) (MSW Management Journal, 2026)
India's National Education Policy 2020 (NEP 2020) represents a landmark reform in the country's educational landscape. While it addresses various aspects of the education system, a critical concern it seeks to tackle is the proliferation of shadow education, often referred to as "coaching culture" in the Indian context. NEP 2020 recognizes the prominence of shadow education and its implications on educational equity and quality. Consequently, the policy encourages the integration of technology in education, early childhood care and education, formative assessment and flexible board exams for reducing the need of coaching among students. This research investigates the key provisions and strategies outlined in the NEP 2020, aiming to transform India's education landscape by reducing the reliance on shadow education and enhancing the overall quality of formal education. Additionally, this paper delves into the pivotal role of India’s rich knowledge system in addressing the escalating issue of shadow education. By examining traditional pedagogical methods and indigenous learning practices, we explore how integrating these time-tested approaches can provide a viable and culturally resonant solution to mitigate the prevalence of shadow education. This exploration contributes to a deeper understanding of the intrinsic strength that has fueled India's intellectual prowess across generations.